Analisis Efektifitas Simpang U-Turn pada Jl. Letjen Suprapto Menggunakan Metode Manual Kapasitas Jalan Indonesia 1997 (Studi Kasus U-Turn Sp Plaza Batam) - Karuniansyah, Muhammad Fadhil (Jurnal Proyek Teknik Sipil, 2023)
U-Turns are employed as a particular access for drivers who want to switch lanes while they're moving. However, the problem that often occurs is that this intersection can be the main cause of congestion on a road. In the case of the U-Turn intersection of Arterial Road Jl. Letjen Suprapto, to be exact, is across from SP Plaza Batu Aji. Traffic jams are often caused by this, especially in the afternoon during work hours. in accordance with the 1997 Indonesian Highway Capacity Manual, This study tries to evaluate the intersection's performance and determine whether it is the primary cause of persistent traffic congestion. The technique used to obtain data is observation and documenting. The results showed that the road capacity value was 2884.1 pcu/hour. Traffic volume value in the direction of Muka Kuning - Tg. Uncang of 1458.7 pcu/hour. 2475.4 pcu/hour in the opposite direction. 1033 vehicles were shown at 17:30-18:00 as making U-turns with an average travel time of 08'36". As a result of vehicles making u-turns, delays occur which hinder the passage of vehicles through the road segment resulting in congestion. This is the main cause of congestion on this road section with a road service value of 0.51 or a service level of C. These results indicate that the road segment is still stable, but vehicle speed is starting to be controlled. The research's conclusions can act as a guide for further investigation.